Restoring the ‘Georgian House’: Architecture, Politics, and Identity in 1970s Edinburgh - James Legard (Angles, 2023)
The National Trust for Scotland’s restoration of 7 Charlotte Square as a museum of the Georgian New Town was both more and less than an exemplary restoration of a townhouse at the centre of Robert Adam's great neoclassical urban set piece. It was conceived and executed in 1972-5, a moment pregnant with significance for Scotland’s – and the United Kingdom’s – political and cultural identity. Lord Kilbrandon’s Commission on the Constitution was about to report and was widely expected to usher in dramatic changes to the relationship between Scotland and the wider Union. At the same time negotiations for the UK’s entry into the then European Community were on the point of bearing fruit. Completion of the restoration was, moreover, timed to coincide with European Architectural Heritage Year and with the UK’s first European referendum. This paper will set the creation of the ‘Georgian House’ in this exceptional context, exploring how it became the vehicle for a distinctive vision of Scotland’s past and future, and then setting out the consequences – and the many compromises to good practice – that resulted from this unavowed but omnipresent agenda. In particular, it will show how the National Trust for Scotland’s leaders – almost all drawn from the country’s well-connected social elite – sought to make use of the prestige of eighteenth-century taste and cultural achievement to carve out a new place for Scotland’s cultural and spiritual heritage, and, perhaps no less importantly, for themselves, in a rapidly changing world.